CORRELATION OF SUPERVISION, OPPORTUNITIES FOR ADVANCEMENT AND JOB SAFETY WITH SATISFACTION OF PUSKESMAS EMPLOYEES IN NORTH KONAWE DISTRICT: English - Saraswati, Putu Suri (Universitas Mandala Waluya Kendari, 2019)
Background: Job satisfaction can motivate an employee health center work, so it will affect the performance of the employee in performing health services for people in the health center. This study aimed to analyze the relationship between surveillance, advanced untu opportunities and job safety of the employee satisfaction Konawe health centers in the North. Methods: This research is a quantitative research with cross sectional study. The population in this study were all employees of health centers in North Konawe as many as 389 people, while the sample size of 194 respondents were collected by stratified random sampling. Data were collected by questionnaire and analyzed using chi square test and Cramer coefficient. Results: The results showed that chi square of supervision = 40,166, opportunities for advancement = 27,353 and job safety = 12,317. The chi square table is 9,488 at ? = 5% and df =4. It means that chi square value > chi square table. Conclusion: There was a relationship between supervision, opportunities for advancement, and job safety with job satisfaction of Puskesmas employees in Konawe Utara Regency.